Abnormalities of endothelial function in patients with predialysis renal failure. Issue 2 (1st February 2000) - Thambyrajah, J; Landray, M J; McGlynn, F J; Jones, H J; Wheeler, D C; Townend, J N
Abstract : BACKGROUND: Endothelial dysfunction plays an important role in the development of atherosclerotic vascular disease, which is the leading cause of mortality in patients with chronic renal failure. OBJECTIVE: To examine the relation between predialysis renal failure and endothelial function. DESIGN: Two groups were studied: 80 patients with non-diabetic chronic renal failure and 26 healthy controls, with similar age and sex distributions. Two indices of endothelial function were assessed: high resolution ultrasonography to measure flow mediated endothelium dependent dilatation of the brachial artery following reactive hyperaemia, and plasma concentration of von Willebrand factor. Endothelium independent dilatation was also assessed following sublingual glyceryl trinitrate. The patients were divided into those with and without overt atherosclerotic vascular disease. RESULTS: Although patients with chronic renal failure had significantly impaired endothelium dependent dilatation compared with controls (median (interquartile range), 2.6% (0.7% to 4.8%) v 6.5% (4.8% to 8.3%); p < 0.001) and increased von Willebrand factor (254 (207 to 294) v 106 (87 to 138) iu/dl; p < 0.001), there was no difference between renal failure patients with and without atherosclerotic vascular disease. Within the chronic renal failure group, endothelium dependent dilatation and von Willebrand factor were similar in patients in the upper and lower quartiles of glomerular filtration rate (2.7% (0.7% to 6.7%) v 2.8% (1.1% to 5.0%); and 255 (205 to 291) v 254 (209 to 292) iu/dl, respectively). Endothelium independent dilatation did not differ between the renal failure or control groups and was also similar in patients with renal failure irrespective of the degree of renal failure or the presence of atherosclerotic vascular disease. CONCLUSIONS: Endothelial function is abnormal in chronic renal failure, even in patients with mild renal insufficiency and those without atherosclerotic vascular disease, suggesting that uraemia may directly promote the development of atherosclerosis early in the progression of chronic renal failure.